Application of Elimination Et Choix Transduisant La Realita (ELECTRE) in Hotel Selection in Palembang City - Fadhlan Jiwa Hanuraga; Yunita Yunita; Nabila Rizky Oktadini (Sriwijaya Journal of Informatics and Applications, 2023)
This study develops software for hotel selection using Elimination Et Choix Transduisant La Realita (ELECTRE). In Elimination Et Choix Transduisant La Realita (ELECTRE) multi-criteria decision-making is based on the concept of Outranking by using paired alternative comparisons based on criteria. The test is carried out by determining the normalization of the decision matrix, weighting the normalized matrix, determining concordance and discordance, calculating the concordance matrix, calculating the discordance matrix, determining the dominant concordance and discordance matrix, determining the aggregate dominance matrix, and eliminating less favorable alternatives. After calculating the Elimination Et Choix Transduisant La Realita, the system was tested using the Technology Acceptance Model (TAM). The test results as measured by the Technology Acceptance Model (TAM) method obtained a value of 87.06% for the use of technology (perceived usefulness) and 85.33% for the ease of use of technology (perceived ease of use).